2010
DOI: 10.1007/s12011-010-8751-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Therapy with Metformin on the Concentration of Certain Divalent Cations in Patients with Non-insulin-Dependent Diabetes Mellitus

Abstract: Research was performed on a group of 30 patients with non-insulin-dependent diabetes mellitus (NIDDM), who never received antidiabetic medication before, and on a group of 17 healthy adults. The patients were administered treatment with metformin, 1,000 mg/day. Plasmatic and urinary concentration of magnesium have been measured, copper and zinc along with the concentrations of glucose, HDL, LDL, cholesterol, tryglicerides, HbA1c, and total erythrocyte magnesium, in advance and after 3 months of treatment. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
3
13
2
Order By: Relevance
“…(Fig. 5) The results are in accordance with our previous data [49] and with few other results that revealed an increased tissue levels of magnesium associated with metformin treatment. [50] However, our study revealed there is still a decreased intraerythrocyte magnesium level when compared to the control group.…”
Section: Copper Zinc and Magnesium In Non-insulin-dependent Diabetessupporting
confidence: 92%
“…(Fig. 5) The results are in accordance with our previous data [49] and with few other results that revealed an increased tissue levels of magnesium associated with metformin treatment. [50] However, our study revealed there is still a decreased intraerythrocyte magnesium level when compared to the control group.…”
Section: Copper Zinc and Magnesium In Non-insulin-dependent Diabetessupporting
confidence: 92%
“…Although the evidence from pooled randomized trials has been questioned [10], [11], this recommendation reflects the results of the UK Prospective Diabetes Study (UKPDS), the longest and amongst the largest such trials to date, which showed metformin to have favorable effects on cardiovascular disease independent of blood glucose lowering [12], [13]. If metformin has cardiovascular benefit, or even if its effect is neutral [10], [11], this would appear inconsistent with evidence from human studies that metformin reduces serum magnesium [2], [4], [14], [15] and maintains diabetes-associated hypomagnesemia [3], [16], effects that would theoretically increase vascular risk [5]–[7]. The influence of metformin on magnesium homoeostasis is, however, complex, with evidence of an increase in intracellular magnesium [16], [17] that may offset the potential adverse effects of hypomagnesemia.…”
Section: Introductionmentioning
confidence: 99%
“…If metformin has cardiovascular benefit, or even if its effect is neutral [10], [11], this would appear inconsistent with evidence from human studies that metformin reduces serum magnesium [2], [4], [14], [15] and maintains diabetes-associated hypomagnesemia [3], [16], effects that would theoretically increase vascular risk [5]–[7]. The influence of metformin on magnesium homoeostasis is, however, complex, with evidence of an increase in intracellular magnesium [16], [17] that may offset the potential adverse effects of hypomagnesemia. In addition, there may be other major influences on magnesium metabolism in diabetic patients, including renal disease, gastrointestinal disorders, and a variety of other drugs that lower serum magnesium including alcohol, diuretics and proton pump inhibitors [18].…”
Section: Introductionmentioning
confidence: 99%
“…15 Metformin reduces serum magnesium 3,16 and maintains diabetes-associated hypomagnesemia. 17 The influence of metformin on magnesium homeostasis is, however, complex, with evidence of an increase in intracellular magnesium. 17,18 PPIs belong to the most widely prescribed classes of drugs in the world.…”
Section: Discussionmentioning
confidence: 99%
“…17 The influence of metformin on magnesium homeostasis is, however, complex, with evidence of an increase in intracellular magnesium. 17,18 PPIs belong to the most widely prescribed classes of drugs in the world. In 2006, two cases of PPI-induced hypomagnesemia were published by Epstein and coll.…”
Section: Discussionmentioning
confidence: 99%